Peningkatan Aktivitas Belajar Mahasiswa melalui Model Pembelajaran Kooperatif disertai Mind Mapping - Titin Titin; Reni Marlina (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The lessons that have been conducted so far have not been well optimized assessed from the point of view of lecturers and students. Learning that have been conducted is a teacher centered learning. Student activities tend to be passive, most of the students are just coming, sitting, listening, silent and lack of spirit while following the learning process. This study aims to improve student learning activity in the third semester class of Biology Education Study Program of Tanjungpura University through cooperative learning model with mind mapping in Environmental Studies. Classroom Action Research is used as the method of the research.  Non test by observationsheet is used as the method for collecting data .Data analysis that conducted in this research is qualitativedescriptive studies. The result of the research shows that there is an increase of students' learning activity by reading, notice the pictures, questioning, discussing, giving suggestions, listening actively, writing the results of activities, drawing the mind map, presenting and displaying the mind mapping work with the average result of first cycle 72.27% and 87.38% for the second cycle. The result of data analysis shows cooperative learning model along with mind mapping can increase student learning activity.